2011
DOI: 10.1093/annonc/mdq418
|View full text |Cite
|
Sign up to set email alerts
|

Primary mediastinal B-cell lymphoma treated with CHOP-like chemotherapy with or without rituximab: results of the Mabthera International Trial Group study

Abstract: In young patients with PMBCL (age-adjusted International Prognostic Index 0-1), rituximab added to six cycles of CHOP-like chemotherapy increases response rate and EFS to the same extent as other DLBCL. The combination of rituximab with CHOP chemotherapy is an effective treatment in PMBCL with good prognosis features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
151
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(163 citation statements)
references
References 31 publications
5
151
2
5
Order By: Relevance
“…Similar to our results, the addition of rituximab to chemotherapy minimized the development of primary refractory disease (3% versus 24%; p ϭ .006) and resulted in higher 3-year PFS (88% versus 64%; p ϭ .006) and EFS (78% versus 52%; p ϭ .012) rates, but the OS rate was only slightly greater (89% versus 78%; p ϭ .16). Although derived from an unplanned subgroup analysis, these data provide the strongest evidence to date for the superiority of R-CHO(E)P over CHO(E)P in the treatment of PMLBCL patients [41]. However, a significant number of patients with PMLBCL (22%-59% in various studies) actually have a high-intermediate or high risk aaIPI score and do not fall into the patient population examined in MInT.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar to our results, the addition of rituximab to chemotherapy minimized the development of primary refractory disease (3% versus 24%; p ϭ .006) and resulted in higher 3-year PFS (88% versus 64%; p ϭ .006) and EFS (78% versus 52%; p ϭ .012) rates, but the OS rate was only slightly greater (89% versus 78%; p ϭ .16). Although derived from an unplanned subgroup analysis, these data provide the strongest evidence to date for the superiority of R-CHO(E)P over CHO(E)P in the treatment of PMLBCL patients [41]. However, a significant number of patients with PMLBCL (22%-59% in various studies) actually have a high-intermediate or high risk aaIPI score and do not fall into the patient population examined in MInT.…”
Section: Discussionmentioning
confidence: 93%
“…In the context of the MabThera International Trial (MInT) [17], 87 patients with good-prognosis PMLBCL (bulky stage I or stage II-IV and aaIPI score of 0 or 1) aged Ͻ60 years received six cycles of chemotherapy versus rituximab plus the same chemotherapy (Table 4) [40,41]. More than 90% of patients received R-CHOP or R-CHOEP; etoposide (R-CHOEP) was used in 45% of these patients Figures do not sum to 68 and 16, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have obtained contradicting results, chemoradiotherapy is likely to be superior to single modality therapy, which may be advantageous for localized unifocal bulky sites of disease, which allows a shorter chemotherapy course (1,30,35), or for multifocal disease in relapsing cases (36). Anthracycline-containing chemotherapy has become the standard therapy of DLBCL, while numerous studies have demonstrated increased long term remission rates with the incorporation of rituximab (33,(37)(38)(39)(40)(41)(42). Based on the aforementioned findings, chemotherapy plus rituximab (immunochemotherapy) is currently considered to be the first-line treatment for CD20-positive DLBCLs.…”
Section: Discussionmentioning
confidence: 99%
“…Although not as thoroughly studied as in DLBCL [21,22], multiple analyses have indicated an improvement in PMBCL outcomes when rituximab is added to a polychemotherapy backbone in this CD201 lymphoma [5,23,24]. This, coupled with concern regarding long-term sequelae of RT, have led some authors to question the utility of radiotherapy when rituximab is added to standard chemotherapy [4,25].…”
Section: Discussionmentioning
confidence: 99%